2017
DOI: 10.1186/s12864-017-3978-x
|View full text |Cite
|
Sign up to set email alerts
|

Succinyl-proteome profiling of Dendrobium officinale, an important traditional Chinese orchid herb, revealed involvement of succinylation in the glycolysis pathway

Abstract: BackgroundLysine succinylation is a ubiquitous and important protein post-translational modification in various eukaryotic and prokaryotic cells. However, its functions in Dendrobium officinale, an important traditional Chinese orchid herb with high polysaccharide contents, are largely unknown.ResultsIn our study, LC-MS/MS was used to identify the peptides that were enriched by immune-purification with a high-efficiency succinyl-lysine antibody. In total, 314 lysine succinylation sites in 207 proteins were ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 52 publications
0
33
0
Order By: Relevance
“…Dysregulation of succinate metabolism can cause accumulation of succinyl-CoA, which may induce lysine succinylation (Peyssonnaux et al, 2007;Zhang et al, 2011;Xie et al, 2012;Park et al, 2013;Weinert et al, 2013). The enzyme responsible for succinylation has yet to be identified, and indeed, it is possible that this reaction occurs non-enzymatically by direct reaction between succinyl-CoA and the modified protein (Feng et al, 2017). It is evident that succinylation can modulate macrophage function.…”
Section: Introductionmentioning
confidence: 99%
“…Dysregulation of succinate metabolism can cause accumulation of succinyl-CoA, which may induce lysine succinylation (Peyssonnaux et al, 2007;Zhang et al, 2011;Xie et al, 2012;Park et al, 2013;Weinert et al, 2013). The enzyme responsible for succinylation has yet to be identified, and indeed, it is possible that this reaction occurs non-enzymatically by direct reaction between succinyl-CoA and the modified protein (Feng et al, 2017). It is evident that succinylation can modulate macrophage function.…”
Section: Introductionmentioning
confidence: 99%
“…Post-translation modification (PTM) of lysine, a covalent modification involved in various biological processes, is an efficient strategy for increasing the structural and functional diversity of proteins 1 , 2 . To date, a large number of PTMs, including phosphorylation, ubiquitination, acetylation, and succinylation, have been identified in both eukaryotic and prokaryotic species 3 5 . PTMs alter protein functions by modulating their activity, cellular localisation, and domain structure 6 .…”
Section: Introductionmentioning
confidence: 99%
“…But the number of succinylated proteins in Ananas comosus var. bracteatus was much higher than that in strawberry stigmata [23], common wheat [24], rice seeds [25], tomato [26], Taxus×media [27], Brachypodium distachyon [28], Dendrobium officinale [29]. In physiological level, different species and tissues may possess differential profile of succinylation.…”
Section: The Level Of Succinylation In the Wh Parts Of Chimeric Leavementioning
confidence: 95%
“…One possibility is that a functional α-KGDH complex exist in outside of mitochondria. Some study indicated that the component and activity of α-KGDH complex can be readily measured in cytosolic fractions [29]. And experiments have shown that α-KGDH complex can be localized in the nucleus [31].…”
Section: Functional Annotation and Subcellular Localization Of The Sumentioning
confidence: 99%